Analisis Dan Perancangan Sistem Kompensasi UKM XYZ Dengan Metode Adhered Dan Overlapping Berbasis Job Value - Fitri Prambodo, Heiqal; Firas Syafiq, Muhammad; Nurviajie Kurniawan, Rizhan; Fikri Nur Solihin, Muhammad; Dipo Utomo, Prayoga; Kartika, Lindawati (BULLET : Jurnal Multidisiplin Ilmu, 2024)
This research aims to help and provide input to the owners of SME XYZ in mapping salaries using the adhered and overlapping method and using the Hay method in determining compensation factors. The data collection method was carried out through descriptive quantitative research, where respondents were interviewed to obtain employee profile and salary data to analyze the employee salary mapping structure. The analysis results show that the total salary using the adhered method is IDR 75,775,851.05, while with the overlapping method the total salary is IDR 70,998,886.54. which means the difference between the actual salary and the existing method is large.